Radiological difference between arthrosis, erosive osteoarthritis and arthritis of the hands - Bundovska Kocev, Smiljana; Stefanovska, Elizabeta; Antuleska Becheska, Gordana; Lazarevska,Menka; Nikolova, Sonja; Karagjozova, Ivanka (My University, 2021)
OA is defined as non-inflammatory disease with cartilage damage only and formation of a new bone tissue on the damaged surface and joints. RA is chronic, systematic and articular disease with still unknown etiology. To define the radiological signs of RA and to compare them with progressed erosive changes of the hands.
Keywords: ARTROSIS; EROSIV OSTEOARTRITIS; ARTRITIS